Racial and ethnic disparities in COVID-19 mortality in the United States - Javier Prado-Galbarro, Francisco; Estela Gamiño-Arroyo, Ana; Cruz-Cruz, Copytzy; Martínez-Núñez, Juan-Manuel; Sanchez-Piedra, Carlos (Journal of Ideas in Health, 2022)
Background: Among COVID-19–associated deaths reported in the United States (U.S.), minority communities were disproportionately represented. The objective was to assess differences in mortality by race and ethnicity among patients with coronavirus disease 2019 (COVID-19) in the U.S. Methods: This is a retrospective case series study with information extracted from the U.S. Centers for Disease Control and Prevention between January 20 and December 29, 2020. Clinical and sociodemographic data were analyzed by race and ethnicity from non-hospitalized and hospitalized patients with COVID-19. Binary logistic models were fitted to evaluate factors associated with COVID-19-related mortality. Results: A total of 434,076 patients with COVID-19 were characterized; 284,574 cases were Non-Hispanic White, 10,468 cases were Non-Hispanic Asian, and 949,022 cases were Non-Hispanic Black, and 89,407 cases were Hispanic/Latino. For non-hospitalized patients, Hispanic/Latino with pneumonia (OR 3.34, 95%CI: 1.70-6.58) and Non-Hispanic Asian with comorbidities (OR 3.88, 95%CI: 0.99-15.2) had the highest odds for mortality. For hospitalized patients, Non-Hispanic Black with comorbidities (OR 3.02, 95%CI: 2.24-4.08) and Non-Hispanic Asian and Non-Hispanic Black with pneumonia (OR 2.98, 95%CI: 2.09-4.26; and OR 2.97, 95%CI: 2.60-3.38, respectively) had the highest odds for mortality. Conclusion: Racial/ethnic disparities in mortality persist among patients with COVID-19 in the U.S. These findings support the assertion that racial and ethnic minorities are disproportionately affected by COVID-19 in the U.S.